Approval addiction : overcoming the need to please everyone - Meyer, Joyce, 1943- (New York : Warner Faith, 2005)
"Author tackles a lack of self-esteem and the need to please others as a major problem in relationships and offers guidance via Christian belief and values" --Provided by the publisher.
Facing fear and finding freedom -- Knowing who you are -- Conforming to righteousness -- Changing your self-image -- Loving yourself -- Overcoming approval addiction -- Pressing past pain -- Pressing past guilt and shame -- Pressing past anger and unforgiveness -- Pressing past a 'people-pleaser' attitude -- Pressing past rejection -- Breaking controlling powers -- Using your pain -- Conclusion: Living complete in Christ.
Includes bibliographical references (p. [254]-255).
Keywords: Self-esteem -- Religious aspects -- Christianity; Assertiveness (Psychology) -- Religious aspects -- Christianity; Interpersonal relations -- Religious aspects -- Christianity